PENGARUH INTELLECTUAL CAPITAL TERHADAP RETURN ON EQUITY SERTA IMLIKASINYA TERHADAP HARGA SAHAM (Pada Perusahaan Ritel yang Terdaftar di Bursa Efek Indonesia) - Taofiqkurochman, Cecep (JURNAL KEBANGSAAN, 2016)
ABSTRACT The research is purposed to examine the influences of intellectual capital toward return on equity and the impacts on the stock price for Retail Company. The dependent variable for this research is the stock price, return on equity is the intervening variable, and the intellectual capital as the independent variable. All the samples for this research are taken from annual report of Retail Company listed on Indonesia Stock Exchange during 2012-2014 period. Samples were selected by using purposive sampling method and 11 retail companies were obtained which met the samplesâ criteria. The data was analysed by applying path analysis method. The result of this research indicated that partially, the component of intellectual capital which has a significant influence toward the return on equity was the capital employed efficiency only. Meanwhile, human capital efficiency and structural capital efficiency had no significant effect to the return on equity. But simultaneously, the three components of intellectual capital affect the return on equity substantially. This research also showed that return on equity did not essentially influence the price of stocks. Key Words : intellectual capital, return on equity, stock price, path analysis